Perfil das lesões ortopédicas no brazilian jiu-jitsu - Barreto, Adonai Pinheiro (2017)
Brazilian Jiu-Jitsu (BJJ) is a martial art which proposes to control the opponent through falls, immobilizations and joint blocks. The present study aimed to analyze the profile of orthopedic injuries of Jiu-Jitsu fighters in the state of Sergipe.A total of 137 fighters were evaluated, 126 males and 11 females, through the orthopedic and physiotherapy services in the University Hospital at Universidade Federal de Sergipe, as well as in martial art training centers in Aracaju.They presented an average of 5.77 ±5.07 years of sports practice. In addition, 85.4% of the participants already suffered some type of orthopedic injury in jiu-jitsu practice. Being the sprain the most prevalent lesion with 61,5%, and the blue belt athletes with the highest prevalence of injuries (30.8%). The anatomic region most affected was the shoulder (21.7%), followed by the knee (20.5%), hand (12.3%), ankle (11%) and elbow (10.4%). Most of these lesions were considered of mild severity (35,9%), and the treatments most used by them were medications and physiotherapy. They had an average of 21.32 ±14.5 physiotherapeutic sections.